Study of Lpo Levels on the Organs of Experimental Animal Fed with Sildenafil Citrate and Ethanol by using UV–VIS Spectrophotometric Technique - M SREENIVASULU; VIJAY KUMAR CHAVAN (International Journal of Pharma and Bio Sciences, 2018)
Sildenafil citrate is proven to be the best oral treatment. For Erectile dysfunction (ED), a common disorder among men, is on the surge in recent days. Even though many treatments are available, Sildenafil strengthens erectile function and also effective in men with nonvascular organic etiologies y, hypertension, diabetesand psychogenic causes. Sildenafil citrate and ethanol consumption are used in societies world- wide and have been identified as injurious to human health. The aim of this study was to determine Lipid Peroxidation level by using UV–VIS Spectrophotometric technique) Albinomice weighing around 25g made in to seven groups S1 to S7 and exchgoup contains Six mice. They fed with Sildenafil citrate and Ethanol. 50 mg Sildenafil citrate drug dissolved in an appropriate Volume of Conductivity water to get 20 ppm solution. This solution was used as the drug and the animals were fed with this drug at1µg/gm body weight. Ethanol, here, represents 18% or 100ppm of Ethanol and the experimental Albino Mice were fed with this Ethanol solution at 0.01 µg/gm body weight. The animals in the group S1 were considered as control animals and were fed intragastrically with conductivity water. The animals in the group S2 and S3 were fed with a single close of the drug chosen (Caverta) for 15 days and 30 days respectively. The groups S4 and S5 were treated with a single dose of Ethanol for 15 and 30 days respectively and the animals belonging to the last pair of groups (S6 and S7) were treated with a single dose of drug and Ethanol combinedly for 15 and 30 days respectively. The animals belonging to the groups S2, S4 and S6 were sacrificed on 15th day of initial drug administration while those belonging to S3, S5 and S7 were sacrificed on 30th day of initial drug administration. All these experimental animals were decapitated on the terminal day of the dosage, after four hours of drug administration. The operative procedures were carried under strict aseptic precautions. A vertical ventral midline incision was made in the abdominal wall to collect both the left and right testis and Heart samples, after using open Ketalar_anaesthesia. These collected testis samples were examined by using UV-VIS Spectral technique. If Caverta and Ethanol were fed combinedly, the impact has been noticed to be severe on the level of LPO in tissues of Testis and Heart of the experimental animals. There is a heavy surge in the level of LPO and the value was detected to be â‹ 23% and 61% respectively for 15 and 30 days of treatment.-. Therefore, it is concluded that the combined dosage of Caverta and Ethanol produce an enhanced LPO in the tissue of Testis and Heart of experimental Albino mice. It is suggested that the utilization of sophisticated analytical techniques would probably throw limelight on the mechanism of action of these drugs.